2018
DOI: 10.1186/s12905-018-0610-4
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence and abuse against Nigerian women resident in England, UK: a cross- sectional qualitative study

Abstract: BackgroundIntimate partner violence and abuse is a public health problem affecting more than one third of all women globally. It usually takes place between individuals in intimate relationships and/or within the family. In the United Kingdom (UK), while theoretical and policy interventions have led to an increase in intimate partner violence and abuse service provision for women, there is paucity of research on the disclosure and help-seeking practices of women from ethnic minority populations.MethodsA cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 72 publications
(88 reference statements)
2
16
1
2
Order By: Relevance
“…In addition, men used religion to assert gendered expectations on women such that when women resisted expectations of them as a "traditional wife," violence was sometimes used to get them to conform (Gangoli et al, 2020;Mama, 1989;Thiara & Gill, 2012). With regard to disclosure and help-seeking, studies found that the desire to maintain their "honor" within their community, cultural norms acquired through socialization, and gendered power relations were key features in women's narratives of their inability to seek help and escape abusive relationships (Ahmed et al, 2009;Femi-Ajao, 2018;Gill & Harrison, 2019). Similar findings were reported in a scoping review examining sociocultural risk factors affecting domestic violence among South Asian immigrant women in English-speaking countries (Rai & Choi, 2018).…”
Section: Introductionsupporting
confidence: 53%
“…In addition, men used religion to assert gendered expectations on women such that when women resisted expectations of them as a "traditional wife," violence was sometimes used to get them to conform (Gangoli et al, 2020;Mama, 1989;Thiara & Gill, 2012). With regard to disclosure and help-seeking, studies found that the desire to maintain their "honor" within their community, cultural norms acquired through socialization, and gendered power relations were key features in women's narratives of their inability to seek help and escape abusive relationships (Ahmed et al, 2009;Femi-Ajao, 2018;Gill & Harrison, 2019). Similar findings were reported in a scoping review examining sociocultural risk factors affecting domestic violence among South Asian immigrant women in English-speaking countries (Rai & Choi, 2018).…”
Section: Introductionsupporting
confidence: 53%
“…The presence of informal social networks, where religious leaders are part of the collaborative community responses, have been shown effective to improve access, facilitate the utilization of existing IPV services, and changing norms related to it [58,59]. They may also be crucial in responding to the social, emotional, and spiritual needs of IPV victims.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural attitudes however can be pervasive and deep in such areas [33][34][35][36]. Dobash and Dobash [29] discuss the effects of such "hidden" factors, despite legal and policy changes.…”
Section: Historic and Current Effects On Policy Law And Attitudesmentioning
confidence: 99%